PELANGGAN DAN KEPUASAN - Candra Wijaya; Aziza S; Wirda Hasanah (Jurnal Sabilarrasyad, 2020)
The customer is someone who has an important role that can have a positive impact on the organization. Therefore, customers must be privileged by providing what customers expect can be fulfilled. There are 7 factors that affect customer satisfaction, namely: a). Score; b) Competitiveness; c) customer perception; d) Price; e) Imagery; f) Service phase; g) Moment of service; h) The level of customer interest. Customer satisfaction as a state of fulfilling customer needs, in the sense that everything needed can be received in accordance with the desired criteria. The higher the capacity needs are met, the higher the satisfaction it receives. If quality is the desire to satisfy and satisfaction is a sense of pleasure and disappointment over the performance of a product or service produced, then if the quality of service compared with the level of satisfaction obtained a relationship that customer satisfaction with service quality if met will result in acceptance or rejection of service. In other words, it causes satisfaction and dissatisfaction.